Comparative Legal Analysis of the Right to Equal Education for Girls: Indonesia vs. Australia (Statutory and Framework Specificity) - Ni Made Padmawardhani Rakeswari (Westscience Press, 2026)
This article comparatively examines the legal protection of the right to education for women in Indonesia and Australia, focusing on how constitutional ideals are translated into enforceable anti-discrimination measures. While Indonesia’s 1945 Constitution and related statutes formally guarantee the right to education and prohibit discrimination, they largely rely on a general, formal-equality approach that lacks explicit definitions and remedies for gender-based and indirect discrimination. As a result, systemic and institutional barriers faced by girls often remain legally unaddressed. In contrast, Australia’s Sex Discrimination Act 1984 adopts a lex specialis framework that explicitly prohibits both direct and indirect discrimination in education, particularly through Sections 5 and 21, supported by accessible enforcement mechanisms at federal and state levels. This comparative analysis demonstrates a shift from general rights to specific remedies in the Australian system, enabling substantive equality in educational access and experience. The study argues that Indonesia would benefit from targeted anti-discrimination legislation to move beyond formal guarantees toward effective protection and enforcement of gender equality in education.